Ethnoecology of hunting in an "empty forest". Practices, local perceptions, and social change among the Baka of Cameroon - (:unkn) unknown (My University, 2017)
As other tropical forest areas, Central Africa shelters both a high biodiversity and many local communities who depend on it for their subsistence. However, conservation policies enforced in such contexts rarely succeed to conciliate human development and ecosystem sustainability. Conservationists consider subsistence hunting as a major hurdle to wildlife conservation, but for local populations hunting is deeply embedded in cultural identity, diet, economy, and social and symbolic practices. In this context, this thesis examines the tensions between subsistence hunting and defaunation. Defaunation of Central African forests is driven by a multiplicity of factors including the complex entanglement of wildlife in a wide range of apparently incompatible values and priorities. Beyond western concerns regarding ecosystems sustainability and the intrinsic value of animal species, defaunation also generates concerns related to food security, public health (epizootics), indigenous rights, and even national security (in relation to ivory smuggling). Despite these tensions, the understanding of the human and social dimensions of the “bushmeat crisis” remains underexplored.This thesis explores the socio-cultural aspects of hunting and wildlife crisis through data collected during 14 months of fieldwork in two Baka villages of southeastern Cameroon. The Baka live in a context polarized by conservation measures on one side and economic incentives for bushmeat trade on the other. This thesis provides a broad view of how the Baka society reacts to a fast changing context where fauna has become a major stake. To do so, I analysed the way Baka hunt, consume, and commercialize wild meat, but also how they interpret environmental changes and their potential impacts on social structure and wellbeing. Through the different chapters of the thesis, I used an ethnoecological approach and combined data collected through qualitative and quantitative methods. Specifically, I
Keywords: African Research